(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Grain filling determines the grain weight, a major component of grain yield in cereals. Grain filling in barley depends on current assimilation and culm reserves. A pot experiment was conducted at the Grilled House, Department of Crop Botany, Bangladesh Agricultural University, Mymensingh during October 2015–May 2016 to study the grain filling patterns and the contributions of culm reserves to grain yield under drought stress. The experiment consisted of two factors—barley cultivars (six cultivars) and drought stress treatments (control and drought stress). Drought stress was imposed by limiting the irrigation during grain filling period. The tillers were sampled at anthesis, milk-ripe and maturity to determine the changes in dry weights of different parts, viz., leaf lamina, culm with sheath, spikes, and grains; and to examine the contribution of culm reserves to grain yield. The result in this experiment revealed that the grain yield was reduced by 5–25% due to drought stress. The reduction in grain yield was attributable to reduce number of grains per spike and lighter grain weight due to the stress. Drought stress drastically reduced the grain filling duration by about 30% and the stress induced early leaf senescence. Photosynthesis rate and leaf greenness were also reduced in stress. The stress altered the contribution of culm reserves, water soluble carbohydrates (WSCs) in culms to grains. At milk ripe stage, accumulation reached its peak. It accumulated 29.0 to 70.0 mg and from 15.8 to 40.6 mg culm−1 in control and stressed plants, respectively. The residual culm WSCs ranged from 3.5 to 11.2 mg and 1.0 to 3.5 mg culm−1 under control and stress conditions, respectively. The highest contribution of culm WSCs to grain yield was observed in BARI barley2 and the lowest was in BARI barley5 both in control and stress condition. Among the cultivars studied, BARI barley2 produced higher yield with the higher contribution of culm reserves to grain yield under the drought stress. J. Bangladesh Agril. Univ. 16(1): 62-66, April 2018